Evaluating CHARGE syndrome in congenital hypogonadotropic hypogonadism patients harboring CHD7 variants. (August 2018) - Xu, Cheng; Cassatella, Daniele; van der Sloot, Almer; Quinton, Richard; Hauschild, Michael; De Geyter, Christian; Flück, Christa; Feller, Katrin; Bartholdi, Deborah; Nemeth, Attila; Halperin, Irene; Pekic Djurdjevic, Sandra; et al.
Abstract Purpose Congenital hypogonadotropic hypogonadism (CHH), a rare genetic disease caused by gonadotropin-releasing hormone deficiency, can also be part of complex syndromes (e.g., CHARGE syndrome).CHD7 mutations were reported in 60% of patients with CHARGE syndrome, and in 6% of CHH patients. However, the definition ofCHD7 mutations was variable, and the associated CHARGE signs in CHH were not systematically examined. Methods Rare sequencing variants (RSVs) inCHD7 were identified through exome sequencing in 116 CHH probands, and were interpreted according to American College of Medical Genetics and Genomics guidelines. Detailed phenotyping was performed in CHH probands who were positive forCHD7 RSVs, and genotype–phenotype correlations were evaluated. Results Of the CHH probands, 16% (18/116) were found to harbor heterozygousCHD7 RSVs, and detailed phenotyping was performed in 17 of them. Of CHH patients with pathogenic or likely pathogenicCHD7 variants, 80% (4/5) were found to exhibit multiple CHARGE features, and 3 of these patients were reclassified as having CHARGE syndrome. In contrast, only 8% (1/12) of CHH patients with nonpathogenicCHD7 variants exhibited multiple CHARGE features (P = 0.01). Conclusion Pathogenic or likely pathogenicCHD7 variants rarely cause isolated CHH. Therefore a detailed clinical investigation is indicated to clarify the diagnosis (CHH versus CHARGE) and to optimize clinical management.